2007
DOI: 10.1186/1471-213x-7-64
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of genes associated with bovine blastocyst formation

Abstract: Background: Normal preimplantation embryo development encompasses a series of events including first cleavage division, activation of the embryonic genome, compaction and blastocyst formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 72 publications
4
45
0
5
Order By: Relevance
“…Elevated levels of the ATP5A1 transcript have been noted in bovine BCB -oocytes (Torner et al, 2008), which was related to increased metabolic activity of growing gametes. The EEF1A1 gene regulates protein synthesis (Moldave, 1985) and stimulates blastocyst development in cattle (Goossens et al, 2007). In vitro-produced bovine blastocysts contained significantly less transcripts of this gene when compared to their in vivo-derived counterparts, which usually display better quality.…”
mentioning
confidence: 99%
“…Elevated levels of the ATP5A1 transcript have been noted in bovine BCB -oocytes (Torner et al, 2008), which was related to increased metabolic activity of growing gametes. The EEF1A1 gene regulates protein synthesis (Moldave, 1985) and stimulates blastocyst development in cattle (Goossens et al, 2007). In vitro-produced bovine blastocysts contained significantly less transcripts of this gene when compared to their in vivo-derived counterparts, which usually display better quality.…”
mentioning
confidence: 99%
“…These results are consistent with previous reports on the association of MYL6 with blastocyst formation. Goossens et al (2007) reported that MYL6 is highly expressed at the blastocyst stage compared with earlier stages of development and concluded that this gene could be a candidate marker for blastocyst formation. However, no data has been reported on the involvement of the different splice variants of MYL6 in early embryonic development.…”
Section: Resultsmentioning
confidence: 99%
“…Na descrição do método, foi obtido apenas 3 a 5 vezes de multiplicação em uma única etapa, mas com modificações, esta taxa passou para 15 vezes a até 2.500 vezes em uma única etapa (BAUGH et al, 2001;DONNISON;PFEFFER, 2004;EBERWINE, 1996;GINSBERG et al, 2005;GOMES et al, 2003;JENSON et al, 2003;MOLL;DUSCHL;RICHTER, 2004;PHILLIPPS;EBERWINE, 1996;SCHNEIDER et al, 2004; VAN GELDER et al, 1990;WANG E. et al, 2000;WANG, 2005;ZHU;BABA, 2006 (BALASUBRAMANIAN et al, 2007;BUSTIN, 2002;GOOSSENS et al, 2007GOOSSENS et al, , 2005MISIRLIOGLU et al 2006;ROBERT et al, 2002;VIGNEAULT et al, 2007).…”
Section: Metodologias De Estudo Na Embriogêneseunclassified
“…Para fins de cálculo da regulação relativa, o GAPDH foi utilizado como gene de referência por apresentar a melhor eficiência de reação e menor variação de regulação que a H2A.z e o SDHA. Apesar de alguns autores não acreditarem que este seja um bom controle endógeno para estudos em embriões no estádio de pré-implantação por não manter os níveis de regulação constante entre os diferentes estádios (BUSTIN, 2002;ROBERT et al, 2002), trabalhos recentes utilizam o GAPDH como controle endógeno (BALASUBRAMANIAN et al, 2007;GOOSSENS et al, 2007;MISIRLIOGLU et al 2006).…”
Section: Função Molecularunclassified
See 1 more Smart Citation